Espacios de lectura y su incidencia en el desarrollo de los hábitos lectores de los estudiantes de la unidad educativa Ricaurte, de la ciudad de Ricaurte, cantón Urdaneta, provincia los ríos - Álvarez Moreira, Linner Belen (2015)
In the course and development of this research it is aimed at determining the importance that gives the reading spaces, depending on having a development of reading habits which your results will be that students are allowed to investigate on familiar topics and to know, so remove any doubt, reading is a habit and as such it is necessary to help us in academic performance during the learning process dare reading new knowledge are strengthened because reading should be from the very early age here we find a different way to teach reading to know that the reading area is not only a place full of books but a place where the student is comfortable for texts according to their age student of the fifth and sixth years of the Education Unit Canton Urdaneta Ricaurte Province of Los Rios, had 63 teachers and 87 students, plus surveys were applied to the two entities that took the expected result, a remarkable and worrying problem, realizing that teachers should worry more for apply some techniques for the student to call attention to the reading because reading is an essential habits in human life the much learning texts has therefore students must move from learning to read to reading to learn and of course his degree work is performed to get them interested in reading should know that reading feeds the imagination and strengthens the concentration.